Aggregative capacity of experimental anchored Fish Aggregating Devices (aFADs) in Northeastern Brazil revealed through electronic tagging data - Véras, Luísa Queiroz; Capello, Manuela; Forget, Fabien; Tolotti, Mariana Travassos; Véras, Drausio Pinheiro; Dagorn, Laurent; Hazin, Fábio Hissa (Ocean and Coastal Research (Online), 2020)
Catches of pelagic fish associated to anchored Fish Aggregating Devices have been responsible for increases in income, fish consumption, and even cultural identity of artisanal fishing communities in many developing countries worldwide. Nonetheless, in Brazil, aFAD fishing is still poorly developed and studied. In this experiment, FADs were anchored offshore the city of Recife (Northeastern Brazil) to investigate the potential of moored buoys in the aggregation of commercially important pelagic species near the coast, as an alternative fishing site for artisanal fishers. The behavior of acoustically tagged fish was investigated to assess whether they were attracted to the FADs and how long they remained associated to them. The results indicated that, although economically important species were found near the FADs, they did not remain associated for long periods. From the four species tagged, Acanthocybium solandri, Coryphaena hippurus, Thunnus atlanticus, and Caranx crysos, only the two latter were detected at the FADs. Both species presented a preference for a specific FAD, with stronger site fidelity being recorded for C. crysos. This species presented Total Resident Times (TRTs) of more than a month and continuous residence times of more than 14 consecutive days. T atlanticus, on the other hand, remained around the buoys for short time intervals, with a maximum TRT of only two days. Short diurnal excursions far from the FADs and few longer excursions during nighttime were recorded for C. crysos. These results do not support the possible use of moored FADs near the coast of Recife as an alternative fishing site for artisanal fisheries. It is possible that the geomorphological characteristics of the experimental area did not favor the aggregative behavior of large pelagic fish species, such as tunas, around FADs.